APPLICATION OF PROBLEM / PROJECT-ORIENTED TECHNOLOGY TRAINING FOR STUDENTS OF TECHNICAL AND IT SPECIALTIES ON THE EXAMPLE OF THE COURSE “WEBSITE CONTENT MANAGEMENT SYSTEM” - Ozhyndovych , Л. М. (Journal of Information Technologies in Education (ITE), 2019)
The article examines the experience of successful implementation and peculiarities of using problem / project training technologies for students of technical and IT specialties within the course “Website Content Management”. In the course of the course, the project is implemented – a fullfledged functional web site, which helps to master the educational material of the discipline, the formation of general and subject (professional) competences, obtaining the planned program results of training provided by educational programs of specialties, as well as the acquisition of practical skills, support and development of a viable project that is already a professional achievement. Website Content Management Systems course was created using modern technologies of organization of educational activity with wide use of information and communication technologies and an opportunity to determine not only students' educational achievements, but also to show and develop their own creativity and individuality during the project implementation. The course is available on-line, selected free-of-charge educational materials, requirements for the completed project of the web site are developed, the download of the link and presentation of the finished site for evaluation are provided. In order to determine the viability of the project, evaluation criteria have been proposed that are included in the collaborative project evaluation system by faculty and students, and tools have been created to organize and process the evaluation results using Google services. During the course study, it is determined that the formation of general, subject (professional) competences and the provision of software results of training to the types of work on the project. The results of using problem-based / project-based learning technologies as an example of the Web site content management course encourage the development of cross-curricular links and implement interdisciplinary projects, as well as actively implement problem / project-based learning methods in most curriculum disciplines and technical students -specialties.